2015
DOI: 10.7196/sajch.2015.v9i4.929
|View full text |Cite
|
Sign up to set email alerts
|

Persistent and new-onset anaemia in children aged 6 - 8 years from KwaZulu-Natal Province, South Africa

Abstract: Anaemia impairs normal development in children and is implicated as both a cause and an effect of adverse social and economic family circumstances. [1] Global estimates of childhood anaemia indicate that 293.1 million children aged <5 years are anaemic worldwide, with 28.5% of these living in sub-Saharan Africa. [2] This high anaemia burden among children of sub-Saharan Africa is generally attributed to poverty, communicable diseases, food insecurity, HIV and other associated concerns such as access to healthc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
(8 reference statements)
0
5
0
Order By: Relevance
“…Iron deficiency has improved since the SAVACG study conducted in 1994 as the number of persons with iron deficiency decreased from 5% to 1.9% [ 18 , 19 , 20 ]. A recent longitudinal study conducted on children aged 4–6 years and 6–8 years in rural KZN found that out of the 103 children in the study, 37.9% of the children were mildly anaemic, 60.2% were moderately anaemic and 1.9% were severely anaemic [ 54 ]. These study results were in contrast to the results obtained from the 2012 SANHANES-1 study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Iron deficiency has improved since the SAVACG study conducted in 1994 as the number of persons with iron deficiency decreased from 5% to 1.9% [ 18 , 19 , 20 ]. A recent longitudinal study conducted on children aged 4–6 years and 6–8 years in rural KZN found that out of the 103 children in the study, 37.9% of the children were mildly anaemic, 60.2% were moderately anaemic and 1.9% were severely anaemic [ 54 ]. These study results were in contrast to the results obtained from the 2012 SANHANES-1 study.…”
Section: Resultsmentioning
confidence: 99%
“…The study conducted by Gwetu et al [ 54 ] classified anaemia into two target groups 0–59 months (mild: 10–10.9 g/dL; moderate: 7–9.9 g/dL; and severe: <7 g/dL) and 5–11 years (mild: 11–11.4 g/dL; moderate: 8–10.9 g/dL; and severe: <8 g/dL) [ 54 ]. The 2012 SANHANES-1 study classified children under 5 years (mild: 10–10.9 g/dL; moderate: 7–9.9 g/dL; and severe: <7 g/dL) [ 20 ] Gwetu et al [ 54 ] reported that the results of their study were similar to previous national studies such as the SAVAGC and NFCS-FB-1) [ 18 , 27 ], and local studies [ 55 , 56 ]. These all indicated that the prevalence of anaemia ranged from 16.5% to 33% [ 18 , 27 , 55 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…Parasite infection was further sub-divided into pathogenic and non-pathogenic parasites. Pathogenic parasites are associated with clinical symptoms such as diarrhoea, malnutrition, stunting, and cognitive impairment [ 18 , 19 ]. Non-pathogenic parasites are linked with faecal–oral contamination and were considered as an indicator of poor hygiene.…”
Section: Methodsmentioning
confidence: 99%
“…A Kappa of one shows perfect agreement, while zero reveals agreement equivalent to chance. The calculation of Kappa was based on the difference between the size of agreement present (“observed” agreement) compared to the agreement expected to be due to chance alone (“expected” agreement) [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…South Africa has a high prevalence of anaemia in both preschool and school-aged children. Several independent studies have reported the incidence of anaemia in this population group as ranging from 22% to 57% 12,13,14 which is in stark contrast to the 10.7% stated in the South African National Health and Nutrition Examination Survey (SANHANES-1) report. 15 Nutritional deficiencies and malaria have been reported as major causes of childhood anaemia in sub-Saharan Africa.…”
Section: Anaemia In Paediatricsmentioning
confidence: 58%